2020
DOI: 10.1016/j.cub.2020.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Linking Virus Discovery to Immune Responses Visualized during Zebrafish Infections

Abstract: The discovery of new viruses currently outpaces our capacity for experimental examination of infection biology. To better couple virus discovery with immunology, we genetically modified zebrafish to visually report on virus infections. After generating a strain that expresses green fluorescent protein (GFP) under an interferon-stimulated gene promoter, we repeatedly observed transgenic larvae spontaneously expressing GFP days after hatching. RNA sequencing of GFP-positive zebrafish revealed a picornavirus dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 88 publications
(85 reference statements)
1
46
0
Order By: Relevance
“…A recent study reported the creation of a strain that expresses GFP under an interferon-stimulated gene promoter. Here, GFP expression can be used to track immune antiviral response in larvae and thereby provides an ideal platform to develop new strategies for discovering viruses while testing their impact on vertebrate models [ 39 ].
Can zebrafish become a key in vivo model for the study of the molecular mechanisms involved in viral dissemination?
…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported the creation of a strain that expresses GFP under an interferon-stimulated gene promoter. Here, GFP expression can be used to track immune antiviral response in larvae and thereby provides an ideal platform to develop new strategies for discovering viruses while testing their impact on vertebrate models [ 39 ].
Can zebrafish become a key in vivo model for the study of the molecular mechanisms involved in viral dissemination?
…”
Section: Discussionmentioning
confidence: 99%
“…While zebrafish facilities around the world undoubtedly take great care in optimizing water quality in their aquaria, there is some evidence that pathogens are present in water across a large number of centers ( 74 ). A recent study reported evidence of a novel picornavirus-like pathogen transmitted via the environment—leading to spontaneous activation of interferon responses in otherwise healthy animals.…”
Section: What Can We Learn From Interspecies Differences In Animal Momentioning
confidence: 99%
“…Infection was associated with no overt phenotype, but rather was identified using an isg15 transgenic reporter line. Intriguingly, evidence of widespread viral infection was identified in RNAseq datasets from 92 facilities across the world ( 74 ). It would therefore seem that “asymptomatic” zebrafish infection may be relatively commonplace in zebrafish research and act as somewhat of a confounding—although not necessarily unhelpful—factor in studying immune responses in these animals.…”
Section: What Can We Learn From Interspecies Differences In Animal Momentioning
confidence: 99%
See 2 more Smart Citations